Science, Technology and Innovation Policies in Developed and Developing Countries - Trang, Do Huyen (VNU Journal of Science: Policy and Management Studies; Vol 35 No 1DO - 10.25073/2588-1116/vnupam.4150, 2019)
Abstract : Science, technology and innovation (STI) plays different roles in developed and developing countries. In developed countries, STI is considered a driving force for technology innovation and plays a key role in maintaining high economic growth. By contrast, STI’s role in developing countries is quite limited due to underdeveloped economic and social structures as well as strong dependence on foreign technologies. However, as STI has brought great benefits in supporting developing countries’ socio-economic development and industrialization, the awareness of STI’s important role to these countries has recently been increased. The problem now is, how developing countries can build effective STI policies and strategies. To tackle this problem, more attention and resources are being allocated to STI policy making and implementing. Keywords: Policy, science, technology and innovation, developing countries.